2017
DOI: 10.1136/bmjopen-2016-014260
|View full text |Cite
|
Sign up to set email alerts
|

Using a patient decision aid for insulin initiation in patients with type 2 diabetes: a qualitative analysis of doctor–patient conversations in primary care consultations in Malaysia

Abstract: ObjectiveTo investigate whether the use of apatient decision aid (PDA) for insulin initiation fulfils its purpose of facilitating patient-centred decision-making through identifying how doctors and patients interact when using the PDA during primary care consultations.DesignConversation analysis of seven single cases of audio-recorded/video-recorded consultations between doctors and patients with type 2 diabetes, using a PDA on starting insulin.SettingPrimary care in three healthcare settings: (1) one private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…It includes a PDA developed by a group of researchers from the University of Malaya (UM) on insulin initiation targeted at local Malaysians with poorly controlled type 2 diabetes mellitus (T2DM) despite being on multiple oral hypoglycaemic agents. This PDA was developed over the years using the conventional method and has been implemented in selected local public primary healthcare clinics (Poliklinik Kesihatan) in the Klang Valley in Malaysia 9 10…”
Section: Introductionmentioning
confidence: 99%
“…It includes a PDA developed by a group of researchers from the University of Malaya (UM) on insulin initiation targeted at local Malaysians with poorly controlled type 2 diabetes mellitus (T2DM) despite being on multiple oral hypoglycaemic agents. This PDA was developed over the years using the conventional method and has been implemented in selected local public primary healthcare clinics (Poliklinik Kesihatan) in the Klang Valley in Malaysia 9 10…”
Section: Introductionmentioning
confidence: 99%
“…The included studies were published between 2001 and 2020. Four of the 18 studies were undertaken in Australia [ 22–25 ], three in the USA [ 26–28 ], two in Sweden [ 29 , 30 ], Norway [ 31 , 32 ], UK [ 33 , 34 ], New Zealand [ 35 , 36 ], and Belgium [ 37 , 38 ], and one in Malaysia [ 39 ]. For data collection, semi-structured interviews, focus group interviews, telephone interviews, video recordings, and observations were used.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, there was an underrepresentation of studies, including patients with COPD because no studies contained knowledge on the involvement of patients with COPD from the patients’ perspectives and only two from GPs’ perspectives [ 32 , 36 ]. The remaining studies reported on the involvement of patients with TD2 from either the patients’ [ 22 , 23 , 26 , 29 , 31 , 33 , 38 ] or GPs’ [ 24 , 30 , 32 , 36 , 37 ] views or a combination thereof [ 25 , 27 , 28 , 34 , 35 , 39 ]. In Table 2 , the included studies’ characteristics are presented.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin therapy may be required to achieve adequate glycaemic control in some patients, they so called secondary failure to OHA. Some Patients are hesitating to continue insulin, and some have adverse reaction to insulin 7 . There are guidelines existed for shifting patient's treatment regimen form OHA to Insulin ,8,9 but no such guidelines for shifting a patient from insulin to OHA therapy.…”
Section: Introductionmentioning
confidence: 99%